2014
DOI: 10.1063/1.4900938
|View full text |Cite
|
Sign up to set email alerts
|

Green (In,Ga,Al)P-GaP light-emitting diodes grown on high-index GaAs surfaces

Abstract: We report on green (550–560 nm) electroluminescence (EL) from (Al0.5Ga0.5)0.5In0.5P-(Al0.8Ga0.2)0.5In0.5P double p-i-n heterostructures with monolayer-scale GaP insertions in the cladding layers and light-emitting diodes based thereupon. The structures are grown side-by-side on high-index and (100) GaAs substrates by molecular beam epitaxy. At moderate current densities (∼500 A/cm2), the EL intensity of the structures is comparable for all substrate orientations. Opposite to the (100)-grown strictures, the EL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…As noted for the structure grown side by side on (811)A substrate self-organized corrugated quantum wire arrays were observed in the gain region, as it was already discussed previously [15,18]. The (811)A-grown structure emitted however at ~15 nm longer wavelengths than those grown on (211) and (322) and demonstrated no lasing at room temperature.…”
Section: Growth and Structural Characterizationsupporting
confidence: 57%
See 2 more Smart Citations
“…As noted for the structure grown side by side on (811)A substrate self-organized corrugated quantum wire arrays were observed in the gain region, as it was already discussed previously [15,18]. The (811)A-grown structure emitted however at ~15 nm longer wavelengths than those grown on (211) and (322) and demonstrated no lasing at room temperature.…”
Section: Growth and Structural Characterizationsupporting
confidence: 57%
“…The ε zz maps of the barriers indicate that the 4 nm-thick in-plane tensile strained layers contain about 40% of indium that was deduced by using elasticity theory and Vegard's law. We note that some broadening of the interfaces and Indium intermixing with the surrounding matrix can be attributed (at least partially) to the periodic interface corrugation of the (112) surface [27], as even submonolyaer GaP insertions could be resolved in similar structures grown on the (118) surface [17,18]. The ε xx maps in the barriers demonstrate the presence of vertical columnlike in-plane strain variation with amplitude of ∼ ± 0.2% and a period of ∼30 nm.…”
Section: Growth and Structural Characterizationmentioning
confidence: 92%
See 1 more Smart Citation
“…By contrast, HI orientations that lie on the edges of the ST connecting the LI (100) plane to the (111) or (110) planes -such as the (210), (311), and (211) planes-produce surface structures composed of three or more facets. 2,11,14,18 Because HI surfaces within the ST have complex bulk-truncated atomic arrays, only a few of these GaAs planes have been studied for 1DPA formation: the (631), (731), and (531) planes. 7,19,20 Due to this complexity, it is also quite remarkable that some authors have found energetically stable surfaces inside the ST for crystals such as Si, Ge, and GaAs.…”
Section: Resultsmentioning
confidence: 99%
“…The use of InGaAs quantum wells (QW) and quantum dots [6] in combination with the antiguiding VCSEL concept [7] has solved the problem of reliable highspeed oxide-confined VCSELs [8,9] at 850 nm and longer wavelengths. By applying tensile strained wide bandgap layers and the proper use of substrate orientation, potential barriers in the conduction band may be created by preventing leakage of the injected nonequilibrium electrons into the p-doped cladding layers [10]. Presently, the antiguiding VCSEL approach, which allows to increase the oscillator strength of the optical transition [11] due to the suppressed in-plane modes and an option of ultimately narrow λ/2 cavity, is used by key VCSEL manufacturers.…”
Section: Introductionmentioning
confidence: 99%